Non-volatile memory design platform with 3D hybrid integration of CMOS and nano devices - Niu, Chao. (2012)
To study Non-volatile memory (NVM), we do research on several NVM devices. Study Topological Insulator and Race Track Memory, searching for a potentially better structure. Also study on spin transfer torque random access memory (stt-ram) and spin transfer torque magnetoresistive random access memory (stt-mram), comparing different structures of stt-mram with the help of simulation on NVMspice.